PERANCANGAN ULANG KEMASAN CUP KOPI INSTAN BERDASARKAN USER-CENTERED DESIGN - Siswanto, Daniel; Damayanti, Kristiana Asih; Dewi, Vila Sutra Kusuma (Industrial and Systems Engineering Assessment Journal (INASEA), 2011)
Coffee is the favorite drink of many people. A variety of instant coffee products and readyto-drink coffee are available on the market. However, these instant products are not in instant packaging as well. PT Torabika Eka Semesta launched Torabika Sejodoh as an instant coffee cup product. Research and redesign of Torabika Sejodoh packaging cup is conducted by applying the principles of User-Centered Design. Consumers were the research respondents through interviews. These requirement criteria underlined the questionnaires to collect consumer ratings of importance to customer attributes of the instant coffee cup packaging and customer satisfaction performance against Torabika Sejodoh cup packaging. Furthermore, several alternative packaging design were made and selection of cup Torabika Sejodoh alternative packaging designs that considered most appropriate to the needs of consumers was conducted using focus groups. Redesign of the cup packaging is adapted to consumer needs criteria as the main user of the product and rules of the applied packaging can add value to the product.